ANALISIS AKAD MURABAHAH PADA PRODUK CICIL EMAS TERHADAP MINAT NASABAH DALAM PERSEPEKTIF EKONOMI ISLAM PADA BANK SYARIAH INDONESIA KCP JAKABARING PALEMBANG - Putri, Ramanda; Rizka Apriani; Azizah, Latifah Ayu; Bella, Sintia; Azwari, Peny Cahaya (Istinbath, 2024)
Banks have a primary function as collectors and distributors of funds, while additional services act as supporters. The presence of Islamic banking, such as Bank Syariah Indonesia (BSI), is expected to increase economic growth, especially in Muslim-majority countries like Indonesia. BSI was officially launched on February 1, 2021 through the merger of several government-owned Islamic banks. Innovative products, such as BSI Gold Installments, are one of the efforts to attract public interest in Islamic banking services. BSI Gold Installments utilize murabahah and rahn contracts, which are in accordance with sharia principles, to allow customers to own gold in stages with light payments. Gold is chosen because of its stability in value and its ability to fight inflation, making it an attractive investment. This study aims to analyze the BSI Gold Installment product in increasing customer financing, especially at BSI KCP Palembang Jakabaring, using a descriptive qualitative method. The results show that service excellence, product innovation, and contract transparency are the main factors in the success of this product in meeting the investment needs of the community. However, challenges remain, including low customer interest due to lack of education and promotion. Therefore, BSI is expected to continue to develop marketing strategies and sharia-based product innovations to increase competitiveness in the banking sector.